Lime-based plasters with combined expanded clay-silica aggregate: Microstructure, texture and engineering properties. (October 2017) - Koňáková, Dana; Čáchová, Monika; Vejmelková, Eva; Keppert, Martin; Jerman, Miloš; Bayer, Patrik; Rovnaníková, Pavla; Černý, Robert
Abstract: Plasters containing lightweight aggregates are mostly characteristic by low bulk density and low thermal conductivity but these favorable properties are often achieved at the expense of mechanical strength. In this paper, lightweight lime-based plasters are designed which have good thermal and mechanical properties at the same time. As their supposed applications include the renovation of surface layers of historical buildings, burnt clay shale is used as pozzolanic admixture to lime. The volumetric ratio of silica sand and expanded clay aggregate (ECA) is varied over a wide range to analyze the effect of ECA on microstructure, texture, and mechanical, thermal and hygric parameters of investigated plasters. The microstructural studies show a more compact interfacial transition zone between the basic lime-pozzolan matrix and ECA, as compared with silica sand, which is the most important factor affecting the properties of studied plasters. Apparently, the surface roughness of ECA grains at first makes possible easier formation of hydration products and later it can support the growth of calcite crystals and CSH amorphous phases. The textural analysis together with the measurement of basic physical properties reveals, as the second principal factor, a substantial increase of open porosity with the increasing ECA dosage; the added pores are mostly within the range of 10 nm to 1 μm. The assessment of the wide range of engineering properties of designed plasters leads to the identification of the lime-pozzolan plaster with the volumetric ratio of 1: 1 between silica sand and ECA as the most appropriate solution. The thermal conductivity of this plaster is two times lower than of the lime-pozzolan plaster with silica aggregates, while the changes in compressive and bending strengths are only marginal. The favorable hygric properties can be considered as another asset. Faster water vapor transport, together with the higher water vapor adsorption capability, can decrease a risk of water condensation and moderate the effects of both exterior and interior climate, the relatively slow liquid water transport is a limiting factor for rainwater penetration. The economical parameters of the plaster with the best functional properties are also very good. According to the current situation on the Czech market, the price increase is only 3%, as compared with the reference mix.